MEMBANGUN POSITIVE E-WOM MELALUI E-SERVICE QUALITY, KEPERCAYAAN DAN KEPUASAN - Kartika, Yani; Shihab, Muchsin Saggaff (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
The purpose of this study is to analyse antecedents of positive electronic word-of-mouth (e-WOM). Data were collected using a set of questionnaire distributed to the target respondents of Lazada Indonesia, an e-commerce company in the country. The online questionnaire is of screening questions, the socio-demographic items and the items of constructs. Using a purposive sampling technique, a total of 200 respondents were obtained. Findings show that e-service quality, customer satisfaction and trust are the boosters of positive e-WOM. This examination is hoped to give empiric understanding to the marketers to create positive e-WOM.